Pengaruh Pembayaran Cash On Delivery (COD), Harga Produk, Dan Kualitas Produk Terhadap Keputusan Pembelian Di Tiktok Shop (Studi Kasus Pada Mahasiswa UNISMA) - Silvia Titasari; Muhammad Ridwan Basalamah; Tri Sugiarti Ramadhan (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine and analyze the relationship between cash on delivery payments, product prices, and product quality on purchasing decisions at the tiktok shop. This study used a case study on unisma students where the data was obtained by distributing questionnaires via the g-form to unisma students who were selected by purposive sampling. Determining the number of samples in this study used the Malhotra formula and the results obtained were 85 respondents. The analytical method used in this study is instrument test, (validity test, reliability test), normality test, classic assumption test (multicollinearity test, heteroscedasticity test), multiple linear regression analysis, hypothesis testing (F test and t test), coefficient test determination (Adjusted R2) data processing using the IBM SPSS 25 program. The results of this study indicate that the influence of cash on delivery payments, product prices, and product quality simultaneously influence purchasing decisions. Cash on delivery payments partially have no effect on purchasing decisions, product prices partially have no effect on purchasing decisions, product quality partially influences purchasing decisions.  Keywords: Cash On Delivery Payments, Product Prices, And Product Quality On Purchasing Decisions At The Tiktok Shop